The electronic cigarette phenomenon: prevalence, knowledge and opinion of health care professionals in Italy - De Clemente, Antonietta; Frigerio, Simona; Clari, Marco; Bergese, Ilaria; Lanzarone, Salvatore; Ponticelli, Elena; Scavino, Enrica (La Medicina del Lavoro, 2016)
Background: Electronic cigarette smoking is spreading among health care professionals. E-cigarette smoke effects on health are not known, especially long-term effects. Aim: The aim of this study was to investigate the phenomenon of electronic cigarettes as regards smoking habits, knowledge and opinions of health care professionals. Methods: A multicentre cross-sectional descriptive study was conducted by administering an online questionnaire to all the health care professionals employed in two hospitals. Results: The population included 800 employees. More than half (66.8%) of respondents believed the e-cigarette is potentially harmful and capable of attracting young people to smoking and 38.8% of respondents believed that it can serve to stop smoking. The male gender was statistically associated with tobacco and e-cigarette smoking (p=0.034). The electronic cigarette was smoked little at the work place. The population studied did not have any specific knowledge about e-cigarettes and asked for specific training; the population knew the ban on the sale of e-cigarettes to underaged and emphasized the importance of specific management guidelines. Conclusions: The results of the study show the predominantly negative opinion of health professionals concerning the use of electronic cigarette. Moreover, the study results contributed to an improvement of the smoking policies in the hospitals studied.